2000
DOI: 10.1177/0887302x0001800106
|View full text |Cite
|
Sign up to set email alerts
|

Fashion Leaders' and Followers' Attitudes Toward Buying Domestic and Imported Apparel

Abstract: Using the Fishbein Attitude Model as the conceptual framework, this study investigated whether female fashion leaders and fashion followers differed in the importance they gave to 12 selected clothing attributes and in their attitudes toward buying imported and domestic apparel. A random sample of 641 female consumers completed a mailed questionnaire. Results showed that fashion leaders accorded significantly more importance than fashion followers to six apparel attributes: color, attractiveness, fashionablene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
72
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(83 citation statements)
references
References 26 publications
10
72
1
Order By: Relevance
“…This pattern is consistent with research that has specifically examined the extrinsic/intrinsic issue (Hatch & Roberts; Syzbillo & Jacoby; Wheatley et al in Eckman et al, 1990). Beaudoin et al (2000) identified 12 attributes that correlated with attitudes when purchasing apparel, namely: good fit, durability, ease of care, favourable price, comfort, quality, colour, attractiveness, fashionableness, brand name, appropriateness for occasion, and choice of styles. Dickerson (in Beaudoin et al, 2000) investigated the relative importance that consumers attach to five garment attributes when making purchasing decisions, namely: price, care, country of origin, quality, and style.…”
Section: Theoretical Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…This pattern is consistent with research that has specifically examined the extrinsic/intrinsic issue (Hatch & Roberts; Syzbillo & Jacoby; Wheatley et al in Eckman et al, 1990). Beaudoin et al (2000) identified 12 attributes that correlated with attitudes when purchasing apparel, namely: good fit, durability, ease of care, favourable price, comfort, quality, colour, attractiveness, fashionableness, brand name, appropriateness for occasion, and choice of styles. Dickerson (in Beaudoin et al, 2000) investigated the relative importance that consumers attach to five garment attributes when making purchasing decisions, namely: price, care, country of origin, quality, and style.…”
Section: Theoretical Overviewmentioning
confidence: 99%
“…Beaudoin et al (2000) identified 12 attributes that correlated with attitudes when purchasing apparel, namely: good fit, durability, ease of care, favourable price, comfort, quality, colour, attractiveness, fashionableness, brand name, appropriateness for occasion, and choice of styles. Dickerson (in Beaudoin et al, 2000) investigated the relative importance that consumers attach to five garment attributes when making purchasing decisions, namely: price, care, country of origin, quality, and style. Shim and Kotsiopulos (1993) researched the apparel shopping orientation of consumers on the basis of nine factor labels, namely: appearance/fashion conscious, brand conscious, convenience/time-conscious, shopping mall-oriented, local store-oriented, apathetic toward "Made in the USA", catalogue-oriented, economy/price conscious, and credit-oriented.…”
Section: Theoretical Overviewmentioning
confidence: 99%
“…Different consumers have different preferences for sensory forms of information and use different criteria to interpret identical sensory information provided by clothing fashions (Peck and Childers 2003;Workman and Caldwell 2007). For example, fashion leaders consider the image or symbolic (visual) aspects of apparel more important than do fashion followers (Beaudoin et al 2000). Further, fashion leaders considered visual product aesthetics more central to evaluation of apparel products than fashion followers did (Workman and Caldwell 2007).…”
Section: Fashion Leadership and Sopmentioning
confidence: 99%
“…High fashion leaders are the first to buy and wear new fashions, persuading others to follow [41]. Research shows that fashion leadership purchasers differ in many consumer behaviors, including their evaluation and purchasing of products [7,[17][18][19][20][21]42]. …”
Section: Fashion Leadershipmentioning
confidence: 99%
“…Research has investigated the influence of clothing attributes on consumers' purchase intentions and found that consumers are significantly influenced by different attributes when determining overall acceptance of fashion products [12][13][14][15][16]. In the case of fashion items, an additional consideration is fashion leadership which influences product evaluation and purchasing of products [7,[17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%